Changes in cell adhesivity and cytoskeleton-related proteins during imatinib-induced apoptosis of leukemic JURL-MK1 cells - Kuželová, K; Pluskalová, M; Grebeňová, D; Pavlásková, K; Halada, P; Hrkal, Z (Journal of cellular biochemistry, 2010)
The fusion protein Bcr-Abl, which is the molecular cause of chronic myelogenous leukemia (CML) interacts in multiple points with signaling pathways regulating the cellular adhesivity and cytoskeleton architecture and dynamics. We explored the effects of imatinib mesylate, an inhibitor of Bcr-Abl protein used in front-line CML therapy, on the adhesivity of JURL-MK1 cells to fibronectin and searched for underlying changes in the cell proteome. As imatinib induces apoptosis of JURL-MK1 cells, we used three different caspase inhibitors to discriminate between direct consequences of Bcr-Abl inhibition and secondary changes related to the apoptosis. Imatinib treatment caused a transient increase in JURL-MK1 cell adhesivity to fibronectin, possibly due to the switch off of Bcr-Abl activity. Subsequently, we observed a number of changes including a decrease in cell adhesivity, F-actin decomposition, reduction of integrin β1, CD44, and paxillin expression levels and a marked increase in cofilin phophorylation at Ser3. These events were generally related to the proceeding apoptosis but they differed in their sensitivity to the individual caspase inhibitors.
Keywords: nádorové buněčné linie; Cell Adhesion; apoptóza; průtoková cytometrie; fluorescenční mikroskopie; Benzamides; Microscopy, Fluorescence; Imatinib Mesylate; fibronektiny; Electrophoresis, Gel, Two-Dimensional; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Paxillin; Cell Line, Tumor; benzamidy; Pyrimidines; Antineoplastic Agents; pyrimidiny; western blotting; Flow Cytometry; Blotting, Western; paxilin; protinádorové látky; Fibronectins; Humans; chronická myeloidní leukemie; imatinib mesylát; 2D gelová elektroforéza; Piperazines; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; spektrometrie hmotnostní - ionizace laserem za účasti matrice; buněčná adheze; piperaziny; Tropomyosin; tropomyosin; lidé; Apoptosis